2007
DOI: 10.1111/j.1558-5646.2007.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Specialization and Local Adaptation of a Fungal Parasite on Two Host Plant Species as Revealed by Two Fitness Traits

Abstract: We investigate the geographic pattern of adaptation of a fungal parasite, Colletotrichum lindemuthianum, on two host species, Phaseolus vulgaris and P. coccineus for two parasite fitness traits: infectivity (ability to attack a host individual) and aggressivity (degree of sporulation and leaf surface damage). Using a cross-inoculation experiment, we show specialization of the fungus on its host species of origin for both traits even when fungi, which originated from hosts growing in sympatry, were tested on sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 99 publications
2
47
1
1
Order By: Relevance
“…Although little is known of the causal relationships between infectivity and host mortality in most of the individual fungal species, particularly for host tree species (but see Sahashi et al 1995;Packer and Clay 2000;Augspurger and Wilkinson 2007;Seiwa et al 2008), the observed distant-dependent attacks by the predominant diseases (including several fungi) may suggest that generalist pathogens with broad host ranges may cause seedling mortality in a host-specific manner in this forest community. Recently, Sicard et al (2007) found that both infectivity and the degree of leaf damage by the pathogen Colletotrichum lindemuthianum differed among individual host populations and among host plants, because the pathogens were adapted to the local genotypes of the host plant. Our results, together with evidence of local adaptation (Sicard et al 2007) and negative feedback (Packer and Clay 2004;Kotanen 2007), may suggest that some soilborne pathogens are ubiquitous, but infectiousness and virulence of the pathogens are frequently higher beneath conspecific adults, because generalist pathogens sometimes adapt specifically to their local host populations (Bever 1994;Bever et al 1997;Mills and Bever 1998;Lively and Dybdahl 2000).…”
Section: Primary Killing Agents and The Manner Of Attackmentioning
confidence: 99%
See 2 more Smart Citations
“…Although little is known of the causal relationships between infectivity and host mortality in most of the individual fungal species, particularly for host tree species (but see Sahashi et al 1995;Packer and Clay 2000;Augspurger and Wilkinson 2007;Seiwa et al 2008), the observed distant-dependent attacks by the predominant diseases (including several fungi) may suggest that generalist pathogens with broad host ranges may cause seedling mortality in a host-specific manner in this forest community. Recently, Sicard et al (2007) found that both infectivity and the degree of leaf damage by the pathogen Colletotrichum lindemuthianum differed among individual host populations and among host plants, because the pathogens were adapted to the local genotypes of the host plant. Our results, together with evidence of local adaptation (Sicard et al 2007) and negative feedback (Packer and Clay 2004;Kotanen 2007), may suggest that some soilborne pathogens are ubiquitous, but infectiousness and virulence of the pathogens are frequently higher beneath conspecific adults, because generalist pathogens sometimes adapt specifically to their local host populations (Bever 1994;Bever et al 1997;Mills and Bever 1998;Lively and Dybdahl 2000).…”
Section: Primary Killing Agents and The Manner Of Attackmentioning
confidence: 99%
“…Recently, Sicard et al (2007) found that both infectivity and the degree of leaf damage by the pathogen Colletotrichum lindemuthianum differed among individual host populations and among host plants, because the pathogens were adapted to the local genotypes of the host plant. Our results, together with evidence of local adaptation (Sicard et al 2007) and negative feedback (Packer and Clay 2004;Kotanen 2007), may suggest that some soilborne pathogens are ubiquitous, but infectiousness and virulence of the pathogens are frequently higher beneath conspecific adults, because generalist pathogens sometimes adapt specifically to their local host populations (Bever 1994;Bever et al 1997;Mills and Bever 1998;Lively and Dybdahl 2000). However, we compared pathogenicity between distances for predominant disease symptoms (including several fungi; Appendix 3), instead of individual fungi.…”
Section: Primary Killing Agents and The Manner Of Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…2002; Laine 2005; Niemi et al . 2006; Sicard et al 2007; Springer 2007) (but see Kaltz et al . 1999 for an exception), and from classic boom-and-bust cycles, particularly in agricultural crops, where newly deployed resistance genes increase in frequency but then rapidly lose their effectiveness as pathogens adapt to that new variety (Browning & Frey 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Host and pathogen genotypic interaction effects (GxG interactions) can play a key role in pathogen adaptation to sympatric host genotypes [31-34] as well. Local adaptation is expected in pathogens with dispersal ranges greater than their hosts [18], and there, GxG interactions of pathogen and host genotype may account for a large portion of the variation in pathogen reproductive rate.…”
Section: Introductionmentioning
confidence: 99%